A Novel Framework for Text Recognition in Street View Images - Guzel, Mehmet Serdar (International Journal of Intelligent Systems and Applications in Engineering, 2017)
This paper addresses a new text recognition solution, which is mainly used in detection of street view images. This paper employs two different approaches to detect text based regions and recognize corresponding text fields.Â  The first approach utilizes Maximally Stable Extremal Regions (MSER), whereas the second approach relies on Class Specific Extremal Regions (CSER) algorithm. Two separate frameworks, designed with respect to the aforementioned methods, are applied to the street view images so as to extract text based regions.Â  Numerous experiments were performed to evaluate and compare both approaches. Especially results obtained from ERs based approach are quite encouraging and verify the systemâs ability to detect text based regions and recognize corresponding text fields.